“The foundations of the national glory are in the homes of the people”: the Addison Act, the First World War, and British housing policy - White, C (2018)
This thesis examines the relationship between the First World War and housing conditions in Britain. The Housing, Town Planning, &c.; Act, 1919 – passed immediately after the war following years of investigation and formulation by Christopher Addison and the Ministry of Reconstruction – completely changed the face of British state housing policy. The importance of the war in engendering the first major foray of the state in to the provision of dwellings for the working classes is widely acknowledged, yet the importance of the specific conditions which engendered the policy has not previously been explored. This thesis enriches our scholarly understandings of both the Addison Act and state housing in Britain more widely by closely examining the reciprocal relationship between housing and the First World War in Britain. It builds a more comprehensive picture of the deterioration of housing conditions during the war, and tracks the specific impact they had both on war policy and the plans for reconstruction; in particular, it demonstrates that the Rent and Mortgage Interest (War Restrictions) Act, 1915, was the single most important element in determining the scale of the post-war housing programme. In doing so, it elucidates the myriad challenges the Addison Act faced, and highlights the approaches the Ministry of Reconstruction considered and implemented in an attempt to address them. It draws attention to the hitherto neglected importance of women in the creation of the post-war programme and highlights the influence of pronatalism and the ideas of a healthier future nation on the planning process. Furthermore, closer investigation highlights that for policy-makers in the Ministry of Reconstruction, the housing programme was a ‘silver bullet’: not only did they seek to repair a market irreparably broken by the 1915 Rent Act, but they saw the post-war housing programme as an opportunity through which to fix a wide number of societal problems.